Clinical Evaluation of the 3nethra Aberro Handheld Autorefractometer - Selvamani Perumal; Surya Venkatramanan; Venkatramanan RJ; Jayanthi T; Jai Adithya; Anjaly Abraham; Henna Cherian (Journal of Ophthalmic & Vision Research)
Abstract Purpose: To evaluate the 3nethra aberro auto refractometer device as an alternative tool for quick and reliable measurement of refractive errors and to compare it with the gold standard subjective refractive error measurement. Methods: Refractive errors were measured using both subjective refraction and the 3nethra aberro handheld autorefractometer. The refractive measurements were converted into equivalent vector notations of spherical equivalent and Jackson cross-cylinder measurements J0 & J45. The resultant power vectors were compared with subjective measurements. Results: This clinical study comprised 60 subjects (22 male and 38 female; with a mean age of 34 ± 16 years). Data, when compared with the subjective refraction measurements, resulted in 90% of power vectors values in both left and right eyes being the same in the 3nethra aberro handheld autorefractometer and the subjective measurement. The refractive error measurements also had an agreement of 70% and 90% when the range of diopter was between ± 0.25 and ± 0.5D, respectively. When the Bland-Altman's plot analysis was performed, about 98% of data lied within the ± 2 standard deviation variation. An average correlation between the two methods of error measurement was 0.74, and the paired t-test showed P > 0.05 for all the power vectors except for the spherical equivalent in the right eye. Conclusion: The 90% agreement between the error measurements done by two methods indicates that the 3nethra aberro handheld autorefractometer can function as an alternative for the time-consuming subjective refractive error measurement.